A MORAL VALUE ANALYSIS OF THE WALT DISNEY FILM "TURNING RED" - Yohana Fransiska Laras Ayu Lestari; Luqman Al Hakim (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2023)
This study aims to find out the moral value in “Turning Red” film and to analyze the most dominant moral values appearing in “Turning Red” film. The researcher used qualitative descriptive method. The data from this study comes from “Turning Red” film and the script. In collecting the data, the researcher watched the film, studied the script and the scenes then collected the data by taking notes, the researcher selected and classified the data, put it in the table and verified the data by making conclusion of data findings. To ensure the validity of the data, the researcher used data source triangulation and theory triangulation. The result of this research showed that there are twelve moral values that can be found in “Turning Red” film, such as dishonesty and honesty, courage, peaceability, self-reliance and potential, self-discipline and moderation, fidelity and chastity, loyalty, respect, love, unselfishness and sensitivity, kindness and friendliness, justice and law. The most dominant moral values appearing in “Turning Red” film is love. Keywords: Analysis, Moral Values, Turning Red, Film, Walt Disney